Effects of residual oxygen partial pressure on the degradation of polymer electrolyte membrane fuel cells under reverse current conditions - Eom, KwangSup; Jo, Yoo Yeon; Cho, EunAe; Lim, Tae-Hoon; Jang, Jong Hyun; Kim, Hyoung-Juhn; Hong, Bo Ki; Lee, Jong Hyun (ELSEVIER, 2012)
A PEMFC stack inevitably experiences reverse current conditions during startup and shutdown processes. Residual oxygen partial pressure in the stack affects the local potential in the cathode facing oxygen in the anode and plays a critical role in cathode degradation. In this study, effects of residual oxygen partial pressure on PEMFC degradation were studied under reverse current conditions. Increasing the residual oxygen partial pressure under repetitive reverse current conditions accelerates performance decay and facilitates cathode degradation. Cathode degradation is revealed by an increase in charge-transfer resistance and a decrease in electrochemical active surface area, which can be attributed to corrosion of the carbon support and dissolution/migration and agglomeration of the platinum catalyst. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: INLET RELATIVE-HUMIDITY; CARBON CORROSION; PEMFC DURABILITY; CATALYST; MICROSTRUCTURE; DAMAGE